n-3 PUFA Supplementation Alters Retinal Very-Long-Chain-PUFA Levels and Ratios in Diabetic Animal Models - Gorusupudi, Aruna (Mol Nutr Food Res, 2019)
SCOPE: Long chain (LC)-PUFAs act as precursors for special class of retinal lipids known as Very-long-chain (VLC)-PUFAs and the effect of diabetes on retinal VLC-PUFA levels has been unexplored. In order to understand the supplemental effect of n-3 PUFAs, on decreasing levels of VLC-PUFAs due to diabetes, we chose Nile rat which develops diabetes spontaneously and Akita mouse, a genetic diabetes model. METHODS AND RESULTS: Human retinal punches from donors were collected from eye bank, lipids were extracted and analyzed to study the alterations in VLC-PUFAs and their n-3/n-6 ratios. Nile rats were fed high fat diet to induce hyperglycemia, following which an n-3 PUFA rich diet was fed to the experimental group for two months. Diabetic male Akita mice and WT mice were fed with 5% fish oil mixed in with their chow for two months to observe the effect of n-3 PUFAs. Results indicate that VLC-PUFA levels were lower in human diabetic and retinopathic retinal punches compared to age-matched controls. With supplementation of n-3 PUFAs, there was a significant increase in n-3/n-6 VLC-PUFA ratios in both animal models compared to diabetic controls. CONCLUSION: Dietary supplementation with n-3 LC-PUFAs help to prevent progression of diabetes and associated retinopathy.